THE IMPACT OF RICE HUSK ASH (RHA) AS SOILLESS GROWING MEDIUM ON SAWI CAIXIN GIANT (Brassica parachinensis) GROWTH PERFORMANCE - Nur Faezah Omar; Nur Nasulhah Kasim; Siti Zulaikha Zainal Abidin; Siti Nurlia Ali; Azlan Abdul Aziz (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The Sustainable Development Goal 2 (SDG 2), which aims to end hunger, enhance nutrition, and support sustainable agriculture, places a high priority on food security. The amount of rice husk ash (RHA) produced by the process of burning rice husks has increased over time, causing environmental pollution. In modern soilless agriculture, RHA has a significant potential to be used as a fertile and nutrient-rich medium. The Zero Energy Soilless Agriculture (ZESA) System is a revolutionary concept for horticultural plants that might utilize RHA as a soilless growing medium. The effect of growing medium ratio of cocopeat and RHA on plant growth performance of sawi caixin giant (Brassica Parachinensis) using ZESA system over 35 days was investigated in this study. Three different treatments, T1 (1:0), T2 (1:1), and T3 (3:1), on the growing medium ratio of cocopeat and RHA were carried out. The treatments were set up in four replicates of two individuals each using a randomised full block design. The data of plant Growth parameters such as the number of leaves and plant height were recorded every 7 days, and the fresh weight of the plants was taken on harvesting day. FTIR analysis and an elemental analyzer were used to characterise the chemical analyses of cocopeat, RHA, and fertiliser. As shown by the results, T3 treatment increased all plant growth performance parameters compared to T1 control treatment, with a value of 12.02 cm for plant height, 10 leaves, and 33.75g of fresh weight. The plant growth performance of Brassica parachinensis was improved by using a 3:1 ratio of 25% RHA as a soilless growing medium couple with application of rich nitrogen X and Y fertilisers using the ZESA System. Finally, RHA has the potential to be used as a soilless growing medium for many horticulture plants using the ZESA System.